Early graft failure after coronary artery bypass grafting: diagnosis and treatment - Turk, Tamer (The European Research Journal, 2016)
Early postoperative graft failure after coronary artery bypass grafting (CABG) is still a significant problem that results in high morbidity and mortality. Different therapeutic options are available to manage this complication which include reoperation, balloon angioplasty, angioplasty along with stenting and conservative medical management. Herein, we review the existing literature in diagnosis and treatment options for overcoming early graft failure immediately following CABG.